2011
DOI: 10.1093/mp/ssr016
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock-Regulated Phosphate Transporter PHT4;1 Plays an Important Role in Arabidopsis Defense

Abstract: The Arabidopsis accelerated cell death 6-1 (acd6-1) mutant shows constitutive defense, cell death, and extreme dwarf phenotypes. In a screen for acd6-1 suppressors, we identified a mutant that was disrupted by a T-DNA in the PHOSPHATE TRANSPORTER 4;1 (PHT4;1) gene. The suppressor mutant pht4;1-1 is dominant, expresses truncated PHT4;1 transcripts, and is more susceptible to virulent Pseudomonas syringae strains but not to several avirulent strains. Treatment with a salicylic acid (SA) agonist induced a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 74 publications
1
68
1
1
Order By: Relevance
“…7;Suárez-Ló pez et al, 2001) compared with Col-0. In addition, we recently showed that expression of NPR1 was not affected by the biological clock under our growth conditions (Wang et al, 2011a). Therefore, evidence from our studies did not support a role of the biological clock in regulating WIN3-and NPR1-mediated flowering time control.…”
Section: Win3 and Npr1 Act Additively In Regulating The Transition Tocontrasting
confidence: 74%
See 1 more Smart Citation
“…7;Suárez-Ló pez et al, 2001) compared with Col-0. In addition, we recently showed that expression of NPR1 was not affected by the biological clock under our growth conditions (Wang et al, 2011a). Therefore, evidence from our studies did not support a role of the biological clock in regulating WIN3-and NPR1-mediated flowering time control.…”
Section: Win3 and Npr1 Act Additively In Regulating The Transition Tocontrasting
confidence: 74%
“…For instance, the component of the central oscillator of the Arabidopsis clock, CIRCADIAN CLOCK ASSOCIATED1, was recently shown to play a direct role in plant defense (Wang et al, 2011b). In addition, the expression of some defense genes is also known to be under the control of the biological clock (Wang et al, 2001(Wang et al, , 2011aSauerbrunn and Schlaich, 2004;Weyman et al, 2006). However, we did not detect any change in the expression of the circadian clockregulated gene CO in both win3 and npr1 mutants (Fig.…”
Section: Win3 and Npr1 Act Additively In Regulating The Transition Tomentioning
confidence: 58%
“…Thus, the change of acd6-1 dwarfism induced by second-site mutations could be conveniently used as a visual readout to provide a rapid assessment of the effect of these second-site mutations in some genes on defense responses. acd6-1 has been successfully used in genetic analyses to reveal epistatic relationships between defense mutants and in a genetic screen to identify, to our knowledge, novel defense genes (Song et al, 2004;Lu et al, 2009;Ng et al, 2011;Wang et al, 2011aWang et al, , 2011bWang et al, , 2014a. We found that while acd6-1 sim-1 resembled acd6-1 in plant morphology, acd6-1 smr1-1 and acd6-1 sim-1 smr1-1 were significantly larger than acd6-1 plants (Fig.…”
Section: Smr1 Contributes To Sa-mediated Defensementioning
confidence: 77%
“…We identified a lesion mimic mutant in the background of a transposon insertional mutant for the phosphate transporter gene PHT4;1 20. Positional cloning revealed that the lesion mimic phenotype was not associated with the pht4;1 mutation, but was due to a mutation in the FZL gene.…”
mentioning
confidence: 97%